ANALISIS GAYA BAHASA PERBANDINGAN DALAM SYAIR LAGU-LAGU NIAS - Serli Liana Gulo (Universitas Nias Raya, 2026)
This research is motivated by the uniqueness of the use of language style, particularly comparison language style, which can make the presentation of song lyrics more interesting and create an emotional atmosphere that attracts listeners to enjoy and internalize the songs. Comparison language style is figurative language characterized by the use of words to compare, differentiate, and describe something. The purpose of this research is to describe the comparison language style in the lyrics of Nias songs. This research uses a qualitative approach with content analysis methods. The data sources in this research are fifteen Nias song lyrics. The data collection technique used in this research is documentation. The data analysis technique in this research is content analysis. Based on the research results, it is found that there are comparison language styles in the lyrics of Nias songs, namely personification and simile. The dominant comparison language style in the lyrics of Nias songs is simile. In conclusion, the research findings in the lyrics of Nias songs can serve as an illustration or example for the community and as a learning tool in schools, particularly for students. This research suggests that it can be applied in Indonesian language learning, especially in literature lessons, for teachers and prospective teachers of Indonesian language and literature. It is recommended that Indonesian language teachers use Nias song lyrics as a learning resource in literature lessons. Songwriters should use more figurative language to make the lyrics more unique and interesting. Future researchers should use this research as a reference for conducting relevant studies.